Endoscopic full-thickness resection using an endoluminal-suturing device: a proof-of-concept study - Huberty, Vincent; Leclercq, Loulia; Hiernaux, Martin; Verset, Laurine; Sandersen, Charlotte; Beyna, Thorsten; Neuhaus, Horst; Deviere, Jacques (Endoscopy International Open, 2019)
Background and study aims Endoscopic full-thickness resection (EFTR) is used to achieve R0 resection in difficult situations and as a way to overcome the limitations of endoscopic submucosal dissection. Multiple techniques have been described but adequate tools are still under evaluation. In this study, we evaluated the safety and feasibility of non-exposed endoscopic full-thickness resection using a novel endoscopic suturing device.Materials and methods Full-thickness resections of gastric predetermined lesions were performed on five pigs using the Endomina platform. After creating virtual lesion > 20 mm, sutures were placed around it using this triangulation platform. After tightening the knots, the bulging lesion, internalized into the gastric lumen, was cut with a needle knife.Results R0 resections of large lesions (42 to 60 mm) were achieved in all cases. One perforation occurred and prompted us to improve the procedure by shortening the sutures for more maneuverability and reinforcing the suture line before section. Procedure duration dropped by 50 % between the first case and the fourth case. Histological analysis confirmed successful full-thickness resection of all resected specimens.Conclusion EFTR using this triangulation platform seems feasible for lesions > 20 mm. Additional possible improvements were identified to simplify the procedure before moving to human trials.